Instantaneous reproduction number and epidemic growth rate for predicting COVID-19 waves: the first 2 years of the pandemic in Spain - Llorca, Javier; Gómez-Acebo, Inés; Alonso-Molero, Jessica; Dierssen-Sotos, Trinidad (Frontiers in Public Health, 2023)
Introduction: Several indicators have been used during the COVID-19 pandemic to take control measures. In this article we compare the instantaneous reproductive number and the epidemic growth rate in the Spanish population. Methods: Data on daily numbers of cases, admissions into hospital, admissions into ICU and deaths due to COVID-19 in Spain from March 2020 to March 2022 were obtained; these four indicators were considered as "pandemic state indicators". The instantaneous reproductive number was estimated using the software EpiEstim 2. The epidemic growth rate was estimated as the derivative of the natural logarithm of daily cases respect to time. Both the reproductive number and the growth rate -as "pandemic trend indicators" were evaluated according to their capacity to anticipate waves as "pandemic state indicators." Results: Both the reproductive number and the epidemic growth rate were able to anticipate most COVID-19 waves. In most waves, the more severe the presentation of COVID-19, the more effective the pandemic trend indicators would be. Conclusion: The epidemic growth rate and the reproductive number have different roles in measuring the trend of an epidemic together with daily number of cases or other measures of disease frequency. Naïve interpretations as well as the use of any indicator as unique value to take decisions should be discouraged.